Jan Patočka, Umění a čas, svazek 1–2; JAN PATOČKA, Češi, svazek 1–2: Praha 2004, Oikoymenh, 543 s., 451 s.; Praha 2006-2007, Oikoymenh, 901 s., 415 s. - Havelka, Miloš (Dějiny – teorie – kritika, 2007)
Review.